(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Despite significant advances in modern medicine, tuberculosis continues to be one of the leading causes of infectious morbidity and mortality in the world. MDR tuberculosis of the lungs is particularly dangerous, characterized by the resistance of mycobacteria to the main anti-tuberculosis drugs. This form of the disease is characterized by a severe clinical course, a high incidence of complications and an unfavorable prognosis. The development of neurological complications in MDR pulmonary tuberculosis depends on a number of factors. The most significant of these are considered to be the duration of the disease, the prevalence of the tuberculosis process, the severity of respiratory failure and the degree of chronic intoxication.